2018
DOI: 10.1111/1754-9485.12710
|View full text |Cite
|
Sign up to set email alerts
|

Imaging assessment of rounded atelectasis: A pictorial essay

Abstract: Rounded atelectasis is an increasingly recognized but under-diagnosed and sometimes misdiagnosed pulmonary entity. This pictorial essay will present a broad range of examples of rounded atelectasis across different imaging modalities with inclusion of typical and atypical presentations. These examples will highlight imaging features that allow confident diagnosis and those that warrant further management, such as imaging surveillance, alternate imaging or invasive procedures for histological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Rounded atelectasis is a pulmonary entity that is increasingly recognized but underdiagnosed and sometimes misdiagnosed. Although the exact pathophysiology remains debatable, characteristic imaging appearances of round atelectasis have remained consistent [61]. Round atelectasis is a form of chronic collapse of the lung that usually follows an old pleural injury in the form of effusion or pleuritis, which results in entrapment of the subpleural lung, thereby giving it a rounded appearance radiologically.…”
Section: Discussionmentioning
confidence: 99%
“…Rounded atelectasis is a pulmonary entity that is increasingly recognized but underdiagnosed and sometimes misdiagnosed. Although the exact pathophysiology remains debatable, characteristic imaging appearances of round atelectasis have remained consistent [61]. Round atelectasis is a form of chronic collapse of the lung that usually follows an old pleural injury in the form of effusion or pleuritis, which results in entrapment of the subpleural lung, thereby giving it a rounded appearance radiologically.…”
Section: Discussionmentioning
confidence: 99%
“…Rounded atelectasis (also called atelectatic pseudotumor, folded lung, or Blesovsky syndrome) is a condition extensively reported in human medicine, which describes focal, peripheral lung collapse caused by pleural adhesions and fibrosis secondary to chronic pleural effusions and pleuritis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This condition was first published in the 1960s by Blesovsky who reported that peripheral pulmonary nodules sampled during thoracotomies in humans frequently resembled benign folded lung, which initiated research endeavors for defining the imaging characteristics, etiologies, and pathophysiology of this condition. [1][2][3] Asbestos inhalation is the most documented factor associated with this condition in humans, although all types of pleural effusion can potentially induce it.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Asbestos inhalation is the most documented factor associated with this condition in humans, although all types of pleural effusion can potentially induce it. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Irritating pleural effusions (such as chylous or septic exudative effusions) have however a higher propensity of inducing restrictive pleuritis (also called fibrosing or constrictive pleuritis), by forming inelastic pleural fibrous tissue and adhesions between the parietal and visceral pleura, leading to decreased pulmonary ventilatory capacity and ultimately the development of rounded atelectasis. [16][17][18][19][20][21][22][23] In human medicine, rounded atelectasis on CT has three main characteristics, with the lesions presenting as follows: (1) nodular pulmonary soft tissue attenuations, (2) abutting the visceral pleura and creating an acute angle with the pleural surface, and (3) having tortuous, compressed regional vessels and bronchi entering the nodule (called a comet tail sign).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations